Proton Polarization, Quark-Gluon Plasma and an Atom Model (Global Journal of Science Frontier Research, 2023)
The article deals with experiments performed at the National Laboratory named after. Jefferson, associated with elastic and inelastic collisions of the proton nucleus by an electron beam with an energy of 4.56 GeV. It has been experimentally proved that the local maximum found near 33 GeV during the polarization of protons by an electron flow is associated with the electric polarizability αᴇ and the local maximum found at the Large Hadron Collider, but already at an energy of 28 GeV, during p-p collisions, is associated with the polarization of quark-gluon plasma. Thus, the electric polarizability αᴇ, which is a fundamental property of the proton structure, like size or charge, does not consider the influence of the nuclear polarization of the quark-gluon plasma. This introduces its adjustments to the definition of the polarization radius.
Keywords: physical vacuum; quark-gluon plasma; electron; proton; photon; polarization; resonance